In search of an economic remnant of resistance: 3 Reigns 24:12p-t - West, Gerald O. (HTS teologiese studies, 2022)
This article attempts to discern an economic narrative remnant amidst the dominant ethno-religious narrative concerning the division of the united monarchy. Historical-critical comparison of the MT and LXX highlights the source-critical dimensions of the stories of the division of the united monarchy after the death of Solomon. This is clearly a moment of ideo-theological contestation, as the four variant accounts demonstrate. However, within each of the larger ‘division of the kingdom’ narratives, there is an economic narrative remnant. The focus of this article is on identifying and delimiting this economic narrative remnant within each of the two variant accounts in the MT and the two variant accounts in the LXX. Having identified these four variant narratives, literary-narrative analysis is used in order to delimit an economic narrative remnant (1 Ki 12:1–18, 2 Chr 10:1–18, 3 Reigns 12:1–18, and 3 Reigns 24:12p-t), with a special emphasis on 3 Reigns 24:12p-t. The article then turns to a preliminary socio-historical ideo-theological analysis of 3 Reigns 24:12p-t, in order to situate this variant remnant socio-historically. Finally, the article argues that this particular economic-oriented remnant narrative (3 Reigns 24:12p-t) provides critical resources with which to engage aspects of South Africa’s contemporary post-colonial economic struggle.Contribution: The article identifies an LXX source text within a textual variant, 3 Reigns 24:12p-t, and argues that this source text offers a unique and early emphasis on economic contestation in the division of the ancient Davidic-Solomonic kingdom.